Tuning rigidity and negative electrostriction of multi-walled carbon nanotube filled poly(lactic acid) - Natlita Thummarungsan (2020)
© 2020 Elsevier Ltd Multi-walled carbon nanotubes (MWCNTs) were utilized as an effective filler and dibutyl phthalate (DBP) as a plasticizer in the electro-responsive poly (lactic acid) matrix. Under on and off electric field, the MWCNT/PLA/DBP composites showed electromechanical recoverability with typical fast response times less than 1 min. The 0.1%v/v MWCNT-1200/PLA/DBP possessed the highest positive storage modulus sensitivity value of 1.95 at the electric field strength of 1.5 kV/mm. The storage modulus response with a value close to zero was observed at a MWCNT content between 0.8 and 0.9 %v/v. At high MWCNT concentrations, the storage modulus response became negative definite at high electric field strengths. This negative electrostriction behavior was in contrast to the positive definite electrostrictive responses of other materials. In the bending experiments, the 0.1%v/v MWCNT-2100/PLA/DBP produced relatively higher bending responses and dielectrophoresis forces at electric field strengths below 300 V/mm. At higher electric field strengths and higher MWCNTs contents, the dipole moment interaction was screened resulting in the decreases in the electrostriction, bending response and dielectrophoresis force. Thus, it has been demonstrated here that the MWCNTs induced the negative electrostriction in the plasticized PLA, possibly through the physical screening and free volume.